Customers' satisfaction towards marketing mix of an international hypermarket (Case study of Carrefour Hypermarket, Pulau Pinang) / Fairuz Ayuni Rozaini - Rozaini, Fairuz Ayuni (Faculty of Business and Management, 2010)
This research is about a study on customers' satisfaction towards marketing mix of an International Hypermarket (Case Study of Carrefour Hypermarket, Pulau Pinang). The study aimed to identify major marketing mix, which are product, price, placement or promotion that contributes to the customers' satisfaction at International Hypermarket and the researcher chose Carrefour Hypermarket (French Company) and the study was done at Carrefour Hypermarket, Pulau Pinang.